KERAGAMAN SPESIES LALAT BERDASARKAN LOKASI PENANGKAPAN DI PASAR INDUK JAKABARING PALEMBANG - Yunita Panca Putri (Universitas PGRI Palembang, 2019)
ABSTRACTThe variation of bait used can make the fly interested. Flies eat food eaten by humans everyday, such as sugar, milk, protein, fat and other foods, human waste and blood. Flies also like foods that are undergoing a process of fermentation / decay. Flies that perch on food disrupt performance and potentially carry contaminants and reduce the health quality of food ingredients. Flies can be vectors of diseases that are endemic and need serious handling if an area is found with high density flies, therefore it is known the diversity of species of flies based on the fishing location at the Jakabaring market in Palembang. This study aims to identify the diversity of species of flies found in the Jakabaring Central Market Palembang. The place for sampling flies is the main market of Jakabaring Palembang, while the place of research is conducted at the Laboratory of Biology, Science Center, University of PGRI Palembang. The results obtained were 5 species of flies found in the main market of Palembang's Jababaring namely Muscadomestica, Chrysomyasp., Lucilia sp., Sarcophaga sp., And Fannia sp. and the fish plot is the catching location with the most number of flies found. Keywords: House fly; market of Jakabaring Palembang; Feed / food variationsABSTRAK Variasi umpan yang digunakan dapat membuat lalat tertarik. Lalat memakan makanan yang dimakan manusia setiap hari, seperti gula, susu, protein, lemak dan makanan lain, kotoran manusia dan darah. Lalat juga menyukai makanan yang mengalami proses fermentasi / pembusukan. Lalat yang hinggap pada makanan mengganggu kinerja dan berpotensi membawa kontaminan dan mengurangi kualitas kesehatan bahan makanan. Lalat dapat menjadi vektor penyakit yang endemik dan perlu penanganan serius jika suatu daerah ditemukan dengan lalat kepadatan tinggi, oleh karena itu perlu diketahui keanekaragaman spesies lalat berdasarkan lokasi penangkapan di Pasar Induk Jakabaring Palembang. Penelitian ini bertujuan untuk mengidentifikasi keanekaragaman spesies lalat yang ditemukan di Pasar Induk Jakabaring Palembang. empat pengambilan sampel lalat adalah Pasar Induk Jakabaring Palembang, sedangkan tempat penelitian dilakukan di Laboratorium Biologi, Science Center, Universitas PGRI Palembang. Hasil penelitian diperoleh 5 jenis lalat yang ditemukan di Pasar Induk Jababaring Palembang yaitu Musca domestica, Chrysomya sp., Lucilia sp., Sarcophaga sp., dan Fannia sp. dan lokasi ikan adalah lokasi penangkapan dengan jumlah lalat terbanyak. Kata kunci: Lalat, Pasar Induk Jakabaring Palembang, Variasi pakan / makanan.